Peningkatan Kesadaran Penggunaan Produk Halal di Kalangan Remaja Kota Palangka Raya - Risqika Yuliatantri Paramawidhita; Nurul Hikmah Kartini (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The rise of the circulation of cosmetics and food products in the community, especially among millennial adolescents, is increasingly rife, let alone supported by advances in technology that everything can be obtained only by using a finger on a mobile keypad or other electronic media. Millennial adolescents from observations often pay less attention to the halal of a product whether it is food or cosmetics. People's behavior when buying products is sometimes only based on the orientation of the product they like. In line with the enactment of Law Number 33 of Halal Product Guarantee (RUU-JPH), 2014 which one of the articles states that all products must be halal certified, then halal awareness of a product is absolutely necessary. This is reinforced by the latest Halal Product Guarantee Act (JPH) so that many Halal Examining Institutions (LPH) are now appearing. Therefore, it is very important to conduct socialization and awareness of halal through community service programs. Increased halal awareness is conveyed in a number of materials, namely introduction to halal certification, the latest certification policy, SJH criteria, and halal and thoyyib principles in food and cosmetics products. The results of this training improve participants' understanding of halal awareness. The motivation of young participants who have a small industrial business to do halal certification of their products is also increasing. So that it is necessary to follow up on this activity is the process of halal certification assistance.